The Study of Angptl4-Modulated Podocyte Injury in IgA Nephropathy - Jia, Sha; Peng, Xiaofeng; Liang, Ludan; Zhang, Ying; Li, Meng; Zhou, Qin; Shen, Xiujin; Wang, Yucheng; Wang, Cuili; Feng, Shi; Chen, Jianghua; Ren, Pingping; et al. (Frontiers in Physiology, 2021)
Background. Increasing evidence shows that Angptl4 has an effect on proteinuria in podocytes-injured kidney diseases, however, whether there is a relation between Angptl4 and IgA nephropathy (IgAN) has not researched yet. Methods. Plasma and urine samples were obtained from 71 IgAN patients and 61 healthy controls. Glomeruli from 6 Renal biopsy specimens (3 IgAN patients and 3 healthy controls) were separated to RNA-Seq. Differentially expressed genes (DEGs) related to podocyte and Angptl4 between IgAN patients and healthy controls were done by Limma package. Gene set enrichment analysis (GSEA) was used to determine if there is a statistically significant difference between the two groups. STRING was used to create a PPI network of DEGs. Association analysis between Angptl4 levels and clinical features of IgAN was performed. Results. 33 related to podocyte-related and 23 Angpt4-related DEGs were found between IgAN patients and healthy controls. By overlapping the genes, FOS and G6PC were founded upregulated in the IgAN patients, while MMP9 downregulated in the IgAN patients. Plasma and urine Angptl4 levels were closely related to the degree of podocyte injury and urine protein while not related to protein: creatine ratio. Conclusions. Our findings show that Angptl4 levels in plasma and urine reflect podocyte damage, and therefore may be a promising indicative tool for assessing the severity of IgAN patients to identify and reverse the progression to ESRD.